If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -16 = 6x + -2 Reorder the terms: -16 + 9x = 6x + -2 Reorder the terms: -16 + 9x = -2 + 6x Solving -16 + 9x = -2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -16 + 9x + -6x = -2 + 6x + -6x Combine like terms: 9x + -6x = 3x -16 + 3x = -2 + 6x + -6x Combine like terms: 6x + -6x = 0 -16 + 3x = -2 + 0 -16 + 3x = -2 Add '16' to each side of the equation. -16 + 16 + 3x = -2 + 16 Combine like terms: -16 + 16 = 0 0 + 3x = -2 + 16 3x = -2 + 16 Combine like terms: -2 + 16 = 14 3x = 14 Divide each side by '3'. x = 4.666666667 Simplifying x = 4.666666667
| x-21=7 | | 4x^2=-5 | | -258=m-587 | | x^2-2x+7=7 | | 25+4m=2m+65 | | 68-7x=20x+20 | | x+26=45 | | 8-9x=88-37x | | s-904=-615 | | 8-9x=88-27x | | x-26=45 | | 2x+27=5x-9 | | s-2=31 | | 8(3n-2)=(6n+2)+4 | | -18-4x=6-8x | | 174-4x=23x+18 | | 8a+5a+5b-3b= | | 2x+20=9x-27 | | -16=0.2n | | 3/5=6 | | 122-3x=15x+24 | | 5(3x+1)=4x-8x | | 1+4m+5m^2+2m^3=0 | | 1-3+7=6 | | 5u-10v= | | 12-9x=35-16x | | x^3-9x^2+24x+1=0 | | 4+3*5=x | | 4x-x-2=34 | | 3bc=12+9bc | | s+808=57 | | -(7-4x)=7 |